(untitled) (Reflection and Critique Law Magazine, 2025)
This article investigates the influence of different philosophical currents on truth in the methods of evidence evaluation in criminal proceedings, focusing on the limits and opportunities that each offers for the justification of judicial decisions. The critical analysis of acritical objectivist and constructivist subjectivist models of truth reveals their inadequacies to rationally justify findings of fact. It is argued that a conception of truth grounded in critical objectivism, acknowledging the existence of an objective reality although not fully accessible, aligns better with the principles of due process and the need for rational motivation of criminal decisions. The main objective is to demonstrate that only a theory of truth as critical correspondence, which requires the conformity of narratives with empirically verifiable facts, enables intersubjective and rational control of evidence assessment, contributing to the debate on truth and evidence in criminal proceedings.